ANALISIS PROBLEMATIKA ATAS TANAH WAKAF DI INDONESIA - Rahmatullah, Rahmatullah (UIN Palopo, 2023)
AbstractIndonesia is a large country, with a wide variety of tribes, religions, races and cultures and it is known that the majority of Indonesians embrace the Islamic religion. Wakaf is one of the teachings of Islam that concerns the life of society in the framework of Islamic worship. (ibadah sosial). In fact, the presence of promlematics is associated with the development of society and the management of Wakaf governance, thereby affecting the status of hokum to the utilization or survival of the wakaf object.